BUSINESS PROCESS MANAGEMENT MODEL OF RETAIL ENTERPRISES IN THE CONDITIONS OF SYSTEMIC TRANSFORMATIONS - Любохинець, Лариса; Кліщ, Максим (SWorldJournal, 2025)
The article identifies the main stages in the evolution of the concept of business process management. A comparative analysis of business process management models for retail enterprises in conditions of systemic transformation is carried out, and the mai